Polish Adaptation and Validation of the Revised Illness Perception Questionnaire (IPQ-R) in Cancer Patients - Pasternak, Aneta; Poraj-Weder, Magdalena; Schier, Katarzyna (Frontiers in Psychology, 2021)
The article presents findings from three studies designed to validate and culturally adapt the Polish version of the Revised Illness Perception Questionnaire (IPQ-R), a measure of the cognitive and emotional components of illness representations among oncology patients. The tool is conceptually based on Leventhal’s Self-Regulatory Model (Leventhal et al., 1984, 2001). The results of the study 1 (n = 40) show that it can be successfully used in a Polish cultural context as a reliable equivalent to its original English version (Moss-Morris et al., 2002). Analyses conducted in Study 2 (n = 318) provided good evidence for construct and criterion validity as well as the internal reliability of the IPQ-R subscales. Study 3 (n = 54) revealed that the IPQ-R subscales present good test–retest reliability. Overall, the results show that the Polish version of the IPQ-R provides a comprehensive and psychometrically acceptable assessment of the representation of cancer and can be reliably used in studies involving Polish oncology patients.